QUESTIONNAIRE ON AWARENESS OF PRESEASONAL THERAPY FOR JAPANESE CEDAR POLLINOSIS - Sakaguchi, Kosaku; Seno, Satoshi; Kakiuchi, Hiromu; Dake, Yoshihiro; Enomoto, Tadao (JIBI INKOKA TEMBO, 2001)
Preseasonal therapy for Japanese cedar pollinosis involves taking antiallergic medication about 1 to 2 weeks before the start of airborne pollen scattering. This therapy is well known among doctors but the awareness of patients remains unclear, so we surveyed 1, 109 patients with pollinosis to find out using a questionnaire. We found that 55.5% were aware of preseasonal treatment 40% underwent therapy regardless of nasal symptom severity, and, after treatment, 80% considered therapy effective. Their knowledge of preseasonal therapy came 74% from doctors, and 33% from the mass media.